MicroRNAs and Peroxisome Proliferator-Activated Receptors Governing the Differentiation of Mesenchymal Stem Cells - Huang, Chenglong; Gou, Shiran; Wang, Lei; Huang, Kui; Liu, Lin; Zhao, Wenjie; Zheng, Lige; Xiao, Jingang (Current Stem Cell Research & Therapy, 2016)
Mesenchymal stem cells (MSCs) have the self-renewal ability and the ability to produce multiple differentiation. Elucidating the genetic circuits that govern MSC self-renewal and differentiation is necessary to improve our comprehension of MSCs and their role in regenerative medicine. microRNAs (miRNAs) play important roles in the regulation of transcription, and are strongly linked with MSCs regarding the maintenance of pluripotency properties. Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors that belong to the nuclear hormonereceptor family. Interestingly, PPARs not only regulate glucose metabolism and lipidhomeostasis, but also contribute to cell proliferation, cell differentiation, and cell apoptosis. The aim of the present review was to provide an insight into the roles of miRNAs and PPARs in the differentiation of MSCs. Understanding the miRNA signature interactions in conjunction with the role of PPARs is critical for the development of improved strategies to regulate the differentiation of MSCs.
Keywords: osteogenesis